The role of cultural values and religion on views of body size and eating practices among adolescents from Fiji, Tonga, and Australia. (27th September 2012) - McCabe, Marita P.; Waqa, Gade; Dev, Anjileena; Cama, Tilema; Swinburn, Boyd A.
<x xml:space="preserve">Abstract</x> Objectives This study investigated cultural values related to body image and eating practices in Western and non‐Western societies. Design and Methods In total, 628 Fijian, 463 Indo‐Fijian, 598 Tongan, and 534 Australian adolescents completed measures of cultural values and religious influences in relation to the ideal body and eating practices. Results Fijian and Tongan adolescents were more likely to value a large body. Religious influences were most strongly associated with eating practices for Fijians, Indo‐Fijians, and Tongans. Conclusions The findings support the role of religion in transmitting cultural values regarding eating practices in Pacific Island communities. Statement of contribution What is already known on this subject? Previous research has demonstrated that sociocultural factors shape body image and eating behaviours. Most of this research has been conducted in Western countries. What does this study add? The current study identifies the role of cultural values and religious influences on body image and eating behaviours in a number of different cultural groups. This is the first study to use the same methodology to explore these relationships across Western and Pacific Island communities.